Injustice : why social inequality persists - Dorling, Daniel (Policy Press, 2010)
REVISED EDITION NOW AVAILABLE New Foreword by Richard Wilkinson & Kate Pickett, authors of The spirit level Afterword by Daniel Dorling updates developments in the last year Few would dispute that we live in an unequal and unjust world, but what causes this inequality to persist? Leading social commentator and academic Danny Dorling claims in this timely book that, as the five social evils identified by Beveridge are gradually being eradicated, they are being replaced by five new tenets of injustice, viz: elitism is efficient; exclusion is necessary; prejudice is natural; greed is good and despair is inevitable. In an informal yet authoritative style, Dorling examines who is most harmed by these injustices and why, and what happens to those who most benefit. Hard-hitting and uncompromising in its call to action, this is essential reading for everyone concerned with social justice. REVISED EDITION NOW AVAILABLE New Foreword by Richard Wilkinson & Kate Pickett, authors of The spirit level Afterword by Daniel Dorling updates developments in the last year Few would dispute that we live in an unequal and unjust world, but what causes this inequality to persist? Leading social commentator and academic Danny Dorling claims in this timely book that, as the five social evils identified by Beveridge are gradually being eradicated, they are being replaced by five new tenets of injustice, viz: elitism is efficient; exclusion is necessary; prejudice is natural; greed is good and despair is inevitable. In an informal yet authoritative style, Dorling examines who is most harmed by these injustices and why, and what happens to those who most benefit. Hard-hitting and uncompromising in its call to action, this is essential reading for everyone concerned with social justice.